The Use of Very High-Doses of Baclofen for the Treatment of Alcohol-Dependence: A Case Series - de Beaurepaire, Renaud (Frontiers Media S.A., 2014)
Baclofen, particularly high-dose baclofen, has recently emerged as a treatment of major interest for alcohol-dependence. However, baclofen has many potentially dangerous side effects, and the maximal dose of baclofen that may be used is a matter of discussion. Here, the author analyses the medical charts of the last 100 patients seen in his clinic, 17 of whom have been taking a very high dose of baclofen, which is to say, more than 300 mg/day. The analysis of the charts shows that the very high-doses baclofen were justified in almost all the cases. Side effects are analyzed.